Unobserved Income as a Limiting Factor for Sustainable Social and Economic Development in the Context of Digitalization - Tatyana TKACHEVA; Lubov AFANASYEVA; Alexander PIYALTSEV (Communications of International Proceedings, 2020)
The paper is concerned with unobserved income as a limiting factor for sustainable social and economic development in the context of digitalization. The subject of the research are theoretical and methodological issues of unobserved income as a limiting factor for sustainable social and economic development in the context of digitalization. The purpose of the work is to substantiate a mathematical model reflecting regional differences in correlation between unobserved personal income and some characteristics of innovative digital development of the society on the basis of the analysis of the current state of unobserved income and factors affecting the level of digital and innovative development of the society. The paper reveals the substance of approaches to the implementation of the state policy of sustainable regional development in European countries. The study describes the key units of digital economy functioning which are closely interrelated and affect personal income and social and economic development of territories. Special attention is paid to modern research on the assessment of digitalization regarding Federal districts and economic and social effects of digitalization.
Keywords: Unobserved Economy; Unobserved Personal Income; Shadow Economy; Digital Economy; Sustainable Development.